1998
DOI: 10.1021/np980291d
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-HIV Lancilactone C and Related Triterpenes from Kadsura lancilimba

Abstract: Three new triterpene lactones, lancilactones A (1), B (2), and C (3), together with the known kadsulactone A (4), were isolated from the stems and roots of Kadsura lancilimba. Their structures and stereochemistries were determined primarily from mass and NMR spectral data. Compound 3 inhibited HIV replication with an EC50 value of 1.4 microg/mL and a therapeutic index of greater than 71.4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 6 publications
(5 reference statements)
1
62
0
Order By: Relevance
“…Some compounds earlier isolated from T. avicennioides are hydrolysable tannins that indicated antitrypanosomal activity [12]. However, extensive array of triterpenes has been reported to exhibit diverse biological activities such as anti-HIV-1 activity [13], antimycobacterial activity [11], antifungal and antimicrobial [14,15]; antiulcerogenic, anti-inflammatory, fibrocystic, antipyretic, analgesic, larvicidal, and antiedematous activities [16,17]. Moreover, information on triterpenoidal compounds of T. avicennioides is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Some compounds earlier isolated from T. avicennioides are hydrolysable tannins that indicated antitrypanosomal activity [12]. However, extensive array of triterpenes has been reported to exhibit diverse biological activities such as anti-HIV-1 activity [13], antimycobacterial activity [11], antifungal and antimicrobial [14,15]; antiulcerogenic, anti-inflammatory, fibrocystic, antipyretic, analgesic, larvicidal, and antiedematous activities [16,17]. Moreover, information on triterpenoidal compounds of T. avicennioides is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that the ripe fruits of the two plants exhibit similar actions, and have been primarily used as sedative, tonic agents to replenish and promote the production of body fluid, as well as tonify the kidney to relieve mental strain and for the treatment of hepatitis [2]. Although the fruits of these two plants have been accepted as two different crude drugs by the Chinese Pharmacopoeia since 2000 [2], both plants are found to be a rich source of lignans [3][4][5][6][7] and terpenoids [8][9][10][11] in particular the dibenzocylooctadiene lignans exhibiting various biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…13) For the determination of the absolute configuration at C-22 in compound 1, circular dichroic (CD) measurement was carried out. Since a strong negative cotton effect at 259 nm (De 259 Ϫ1.498, CHCl 3 ) was observed, the absolute configuration at C-22 in 1 was consequently assigned as S-configuration.…”
Section: Resultsmentioning
confidence: 99%
“…However, representatives of this structural type such as schisanlactones, kadsulactone A and lancilactones were isolated previously from the stems and roots of plants such as Schisandra species, 11) Kadsura heteroclita ROXB. 12) and Kadsura lancilimba HOW 13) which are used as folk medicines for the treatment of rheumatism, stomachache and enterogastritis. 12,13) In a hope to isolate new secondary metabolites from the Vietnamese mushroom, which are effective for inhibiting viral protease from human immunodeficiency virus (HIV) and hepatitis C virus (HCV), we investigated phytochemically a triterpene fraction from the fruiting bodies of the cultivated G. colossum.…”
mentioning
confidence: 99%
See 1 more Smart Citation